Identifying accessibility of financing for MSMEs in East Java Indonesia - Maulana, Hartomi; Hastuti, Ely Windarti; Setiartiti, Lilies; Abdul Razak, Dzuljastri; Fachrunnisa, Olivia (UMY Press, 2020)
This chapter examined the extent to which MSMEs have accessibility to their financing in the current situation. Primary data was collected by self-administered questionnaires with a sample of 250 respondents from selected MSME owners in six different regencies in East Java. Descriptive statistics was employed in the analysis. The study revealed that conventional financing is preferred to Islamic financing. The study also indicated that personal savings, categorized as internal financing, are the largest sources of fund for MSMEs surveyed in initial, current and future time. This indicates that MSMEs de-pend highly on their savings for financing their daily business operations. However, the study also indicates that bank loans or external funding are considered to be most accessible, followed by personal savings and loans from relatives. Findings suggest that massive socialization on Islamic finan-cial literacy is absolutely needed to enhance the awareness of MSME owners on Islamic financing products.